Analysis of Estimated Electricity Consumption of Medan City in 2024-2028 Using Fuzzy Mamdani Logic - Gultom, Parapat; Thianujaya, Wendy (Journal of Research in Mathematics Trends and Technology, 2023)
This research employs fuzzy linear programming with Mamdani fuzzy logic to predict electricity consumption in Medan City. Data from the Central Statistics Agency (BPS) for the years 2019-2023, including population, electricity customers, Gross Regional Domestic Product (PDRB), and electricity consumption, were analyzed quantitatively. Data processing involved fuzzification, rule formation, rule composition, and defuzzification, with simulations and testing conducted using MATLAB software. The research findings indicate a forecasting error rate of 1.514%, demonstrating effective performance in predicting electricity consumption. Elasticity analysis reveals that electricity consumption in Medan City is significantly influenced by PDRB, providing crucial insights for future energy planning.